A peep into the transcriptome studies of the industrially important brown algae with special focus on Macrocystis genus - Erika A. Salavarría Palma; Sujay Paul (Revista Peruana de Biología, 2020)
Brown algae are a commercial source of different polysaccharides/hydrocolloids that has been used to produce food, pharmaceutical, and several other useful biotechnological stuff. Nevertheless, transcriptomics has become a tool that not only provides valuable information for the understanding of the physiological processes of a species but also allows the identification of industrially important candidate genes. This study describes the transcriptome of brown algae and their industrial application with a special focus on Macrocystis integrifolia.